An Innovation Value Chain in Project Based Companies: A Study of Indonesian Contractors - Harijanto Setiawan; Ferianto Raharjo; Ay Lie Han (Civil Engineering Dimension, 2020)
Innovation is one of the key success factors of contractors to achieve sustainable business. However, studies about innovation cannot be generalized to all business sectors. Therefore, special study about innovation that focuses on contractors in Indonesia is needed. The study is aimed to explore the process of innovation development in contractors, based on innovation value chain (IVC) approach. The qualitative analysis on the data that is collected from in depth interview with top managers of big contractors in Indonesia is carried out. This study found that innovations are generated mainly by project teams because they are involved directly in the project activities. The next phase is to test the idea of innovation in the selected projects in order to assess whether the innovation works well or not. Finally, the selected innovations will be set as a company standard and will be implemented in the subsequent projects.